Mannose functionalized chitosan nanosystems for enhanced antimicrobial activity against multidrug resistant pathogens. (November 2020) - Ejaz, Sadaf; Ihsan, Ayesha; Noor, Tayyaba; Shabbir, Saima; Imran, Muhammad
Abstract: Escalating antimicrobial resistance is causing a major threat to the public health. Failure of traditional antibiotics urges the development of alternative therapeutics, which include biopolymeric nanosystems with intrinsic antimicrobial potential. In the present study, mannose functionalized chitosan nanosystems (M-CNS) were fabricated through reductive amination of chitosan with mannose and further its ionic gelation. Changes in zeta potential and characteristic peaks in FTIR spectra revealed surface functionalization of chitosan with mannose. Zeta-sizer studies disclosed relatively higher size (180 ± 5 nm) of mannosylated CNS as compared to CNS (162 ± 7 nm). Inversely, the zeta-potential was reduced from +32.2 mV to +25.4 mV for M-CNS. Scanning electron microscopy verified the slight increase in size for M-CNS. Antimicrobial evaluation of designed nanosystems as alternative antibacterial agent was assessed by time-kill, polystyrene adherence and antibiofilm assays against both Gram-positive and Gram-negative pathogens. Results indicated that mannose functionalized CNS inhibited the growth of resistant Escherichia coli and Listeria monocytogenes, while demonstrating anti-adherence and biofilm disruption activity. Furthermore, highly resistant Pseudomonas aeruginosa and Staphylococcus aureus were also susceptible against M-CNS. This study unveiled the potential of M-CNS against pathogenic, multidrug resistant, biofilm forming bacteria; thus, making them an ideal candidate for developing alternative-medicines to cure the emerging resistant infections. Highlights: Intrinsically active chitosan nanosystems (CNS) are effective alternative therapeutics. Reductive amination approach to synthesize mannose functionalized CNS (M-CNS). M-CNS effectively inhibited the growth of Gram-positive and Gram-negative pathogens. M-CNS demonstrated enhanced activity against resistant biofilms. M-CNS hold non-toxic profile based on hemolytic and protein denaturation analyses.